Towards Sustainable Inclusive Education: Challenges and Reconstruction of PAI Learning Methods in Islamic Boarding School Education - Mala, Asnal; Zulkarnain, Zulkarnain; Marpuah, Siti; Badriyah, Laila (Jurnal Tarbiyatuna, 2024)
This study examines how Islamic boarding schools in Indonesia can implement inclusive education to increase tolerance and prevent extremism, while still respecting Islamic values. Using a literature review method, this study analyzes various literature related to inclusivity in Islamic education. The results show that Islamic boarding schools have great potential as institutions that support the values ​​of tolerance, moderation, and cooperation, thus creating a peaceful learning environment. However, challenges such as resistance to curriculum reform and traditional views are also identified. This study concludes that by integrating inclusive practices, Islamic boarding schools can play an important role in building a harmonious society and preventing extreme ideologies. These findings provide strategic guidance for the development of an inclusive education model based on Islamic values, responding to local and global needs in the modern era.